Dampak Lama Penyimpanan Arsip Sampel Formalin-Fixed Paraffin-Embedded (FFPE) dengan Konsentrasi Ribonucleid acid (RNA) yang Diekstraksi Menggunakan Kit Komersial - Nur Eka Wiraditya (MANILKARA: Journal of Bioscience, 2023)
Formalin fixation and paraffin embedding (FFPE) is one method of storing sample records over many years. Sample storage over a long period of time allows for a decrease in RNA quality in the sample. This study determines the difference in RNA concentrations in the 2019 and 2020 sample archives with ng/L units. The sample details are 10 (ten) samples in 2019 and 10 (ten) samples in 2020. This research was conducted in 2021 at the Anatomic Pathology laboratory of FK-KMK UGM. This study shows a significant impact on the archival storage of FFPE samples shown by a decrease in RNA concentration between 2019 and 2020 with an average concentration difference of 12.3 ng/L.